Kryterium estetyczne jako wyznacznik kształtowania wzorów językowych zachowań w "Teoryjej stylu polskiego" Józefy Kamockiej (XIX w.) = Aesthetic criterion as a determinant of shaping language patterns of behaviour in "Teoryja stylu polskiego" (Theory of Polish style) by Józefa Kamocka (19th century) - Jurewicz-Nowak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the article is aesthetic values shaping the linguistic behaviour of Poles in nineteenth-century Polish language. The study is empirical. As a research material, a textbook for learning Polish for school children by Józefa Kamocka was used entitled "Teoryja stylu polskiego" from 1875.
Keywords: Kamocka, Józefa (1830-1897); wartości estetyczne w języku; wzór zachowania językowego; podręcznik; rola kobiet w pedagogice; 19 w.; aesthetic values in language; linguistic pattern of behaviour; textbook; role of women in pedagogy; 19th century